2022
DOI: 10.3390/ani12080963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorogenic Acid on Performance, Anticoccidial Indicators, Immunity, Antioxidant Status, and Intestinal Barrier Function in Coccidia-Infected Broilers

Abstract: The effects of chlorogenic acid (CGA) on growth performance, anticoccidial indicators (oocysts per gram of excreta, cecal lesion score, and bloody diarrhea score), immunity, antioxidant status, and intestinal barrier function in coccidia-infected broilers were investigated. A total of 240 one-day-old Arbor Acres broilers were randomly divided into four groups with six replicates of ten broilers each for 42 days. Four treatments included control diet (non-infected control, NC), control diet +Eimeria infection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…In addition, the histopathological investigation of the intestinal tissues revealed that both diclazuril and F. sycomorus extract may exhibit anticoccidial effects against E. intestinalis. These results could be due to the effect of chlorogenic acid as an anticoccidial, antioxidant, anti-inflammatory and the improvement of intestinal barrier function [21] and the antiprotozoal effect of quercetin [18]. Both chlorogenic acid and quercetin were detected in the F. sycomorus methanolic extract [17][18][19].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, the histopathological investigation of the intestinal tissues revealed that both diclazuril and F. sycomorus extract may exhibit anticoccidial effects against E. intestinalis. These results could be due to the effect of chlorogenic acid as an anticoccidial, antioxidant, anti-inflammatory and the improvement of intestinal barrier function [21] and the antiprotozoal effect of quercetin [18]. Both chlorogenic acid and quercetin were detected in the F. sycomorus methanolic extract [17][18][19].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the anti-inflammatory and antioxidant activities of F. sycomorus may result in a rapid amelioration of the negative effects of coccidiosis in rabbits. Moreover, chlorogenic acid exhibited an anticoccidial effect and an improvement of intestinal barrier function in coccidia-infected broilers [21]. The current study aimed to investigate the potential anticoccidial effect of the methanolic extract of F. sycomorus stem bark on controlling intestinal coccidiosis in growing rabbits, with emphasis on E. intestinalis because of its wide range prevalence and pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorogenic acid (CGA) is a component of HE. Supplementation of 1 g/kg of CGA improved growth performance, immune function, antioxidant status, and intestinal barrier function in coccidial-infected broilers ( 17 ). Dietary CGA supplementation at 1 g/kg improved growth performance and quality and oxidative statuses of meat in pigs subjected or not to oxidative stress induced by dietary oxidized oil ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that dietary supplementation with CGA could improve growth performance and intestinal mucosal antioxidant capacity in piglets by elevating antioxidant enzyme activities, preventing lipid peroxidation, and activating antioxidant signaling pathways ( Chen et al, 2018a , b ; Zhang et al, 2018 ). In broilers, dietary CGA supplementation has been reported to enhance growth performance, alleviate inflammatory response, prevent gut damage, improve intestinal mucosal barrier function, and ameliorate oxidative injury in broilers challenged with Clostridium perfringens or coccidia ( Zhang et al, 2020 ; Liu et al, 2022a ). However, little was known about the antioxidant function of CGA in oxidatively stressed broilers.…”
Section: Introductionmentioning
confidence: 99%